Delayed alveolar bone repair and osteonecrosis associated with Zoledronic Acid therapy in rats: macroscopic, microscopic and molecular analysis - Gustavo Zanna FERREIRA; Edson Virgílio ZEN FILHO; Izabel Regina Fisher RUBIRA-BULLEN; Gustavo Pompermaier GARLET; Carlos Ferreira SANTOS; Paulo Sérgio da Silva SANTOS (University of São Paulo, 2020)
Abstract Objective This study aims to evaluate bone repair and the development of the medication related osteonecrosis of the jaw (MRONJ) associated with the use of zoledronic acid in Wistar rats. Methodology 48 male Wistar rats were divided into four groups: ZA, treated with intraperitoneal zoledronic acid, 0.6 mg/kg every 28 days, totaling five doses; control (C), treated with 0.9% sodium chloride; ZA-surgical (SZA) and C-surgical (SC), submitted to extraction of the right upper molars 45 days after the first application. Alveolar bone repair was evaluated by macroscopic and histological analysis. Protein expression evaluations were performed by qPCR. Results Macroscopic evaluation showed that 91.66% (11) of the animals in the SZA group and 41.66% (5) from the SC group presented solution of epithelium continuity (P<0.05). All animals in the SZA group and none in the SC group had bone sequestration. The area of osteonecrosis was higher in the SZA group than in the SC group (P<0.05). In molecular evaluation, the SZA group presented changes in the expression of markers for osteoclasts, with increased RANK and RANKL, and a decrease in OPG. Conclusion The results highlighted strong and evident interference of zoledronic acid in bone repair of the socket, causing osteonecrosis and delayed bone remodeling.